Achieving Gender Equality in Higher Education: A Case Study of UPN Veteran Jawa Timur Employees - Perbawani, Firsty Chintya Laksmi; Trisnaningtyas, Januari Pratama Nurratri (Future Science, 2023)
Gender inequality remains a prominent and multifaceted issue in Indonesia, spanning across social, economic, and security dimensions. In the context of higher education, these disparities manifest in unequal access to opportunities, differential treatment, and limited access to marginalized gender groups. This study delves into the pressing need to establish a gender-responsive university environment that fosters inclusivity, safety, and equality for all. Focusing on the case study of employees at UPN Veteran Jawa Timur, this research employs a comprehensive mixed-methods approach, integrating surveys, focus group discussions, and qualitative interviews to assess the institution's current state of gender responsiveness. By examining policies, practices, and perceptions, it seeks to identify both the strengths and areas for improvement within the institution's gender equality framework. Furthermore, this study uses indicators of gender-responsive higher education as well as gender equality targets in sustainable development goals as a tool of analysis. This research found that the majority of respondents express the overall adequacy of gender-responsive policies in UPN Veteran Jawa Timur. However, some specific sectors need further attention and refinement, particularly regarding gender-friendly facilities such as nursing room and access for people with disability. The study also underscores the necessity of holistic efforts to navigate the intricate pathways toward a gender responsive university in the future.